Sociology and human rights a Bill of Rights for the twenty-first century - Blau, Judith R., 1942-; Frezzo, Mark.; Sage eBooks (Thousand Oaks, Calif. ; London : Pine Forge, 2012)
This anthology examines the implications that human rights have for the social sciences. It discusses how the 1789 Bill of Rights of the US Constitution should be expanded to encompass fundamental human rights, as most other constitutions already have been.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human rights; Social justice; Globalization -- Social aspects; Constitutional amendments -- United States; Electronic books